(untitled) (Proceedings of Southern Federal University. Philology, 2021)
The article is written at the intersection of two quite different research paradigms – expressive grammar and linguoconflictology. The communicative conflict is produced not only by known conflictogens such as invectives and obscenisms, but also by less vivid and specific means, including grammatical forms different in normativity degree. It is extremely important for the public communication harmonization to develop a methodological construct for measuring verbal conflicts and methods for predictive modeling of the cognitive structures of conflict communication. In this connection, it is important to analyze specific lexicon and grammar units able to become a source of communicative conflict. DOI 10.18522/1995-0640-2021-3-61-73 To outline the range of connotations connection with the possibility of grammatical forms to act as a factor of conflict communication is quite feasible, shown by the example of the morphological categories of gender and number. The terms “conflict-containing”, “conflict-causing”, applied to lexical units, can be extended to separate grammatical forms. Localization of attention on components of non-central zone in the totality of linguistic conflict markers introduces new materials and synthesis to the communicative conflict theory, expands the system of knowledge in the field of linguoconflictology. The same morphological form can be filled with completely different pragmatic content, since grammatical forms can be axiologized, get their own content and functional specifics in the process of expressing the author’s intentions. The conventional values of morphological forms and the permissible limits of their variation are modified according to the conditions of communication and the broad context of the situation. Key words: conflict communication, interpretation of linguistic units, morphological forms, category of grammatical gender, category of number.